2019
DOI: 10.1002/ijgo.12897
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycated albumin, fructosamine, and HbA1c with neonatal outcomes in a prospective cohort of women with gestational diabetes mellitus

Abstract: Objective: To investigate whether glycated albumin, fructosamine, and hemoglobin A1c (HbA1c) are associated with neonatal complications in newborns of pregnant women with gestational diabetes mellitus (GDM). Methods:Between November 2016 and September 2017, women with a singleton pregnancy and GDM were enrolled in a prospective study in an obstetric Portuguese referral center. Glycemic markers were compared between mothers of newborns with and without complications. Multivariable logistic regression models and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Therefore, many researchers question its value as a suitable pregnancy biomarker [23]. However, it has also been reported that the high HbA1c of GDM pregnant women in late pregnancy is related to macrosomia [24]. The clinical analysis of GCP in this study shows that high HbA1c in late pregnancy is an independent risk factor for LGA, while high blood glucose in the same period is not associated with…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, many researchers question its value as a suitable pregnancy biomarker [23]. However, it has also been reported that the high HbA1c of GDM pregnant women in late pregnancy is related to macrosomia [24]. The clinical analysis of GCP in this study shows that high HbA1c in late pregnancy is an independent risk factor for LGA, while high blood glucose in the same period is not associated with…”
Section: Discussionmentioning
confidence: 52%
“…In former times and in veterinary medicine, long-term hyperglycemia (1–3 weeks) is diagnosed by an elevated fructosamine concentration. Different human and veterinary studies show a significant correlation between HbA1c and fructosamine [ 11 , 18 , 20 – 22 ]. This was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sugawara et al 54 consider that when HbA1C is not statistically different, the risk of infant complications increases if GA≥15.80. Mendes et al 55 consider that GA is correlated with the neonatal complications of GDM patients while there is no significant correlation between HbA1C and the neonatal complications of GDM patients.…”
Section: Application Of Glycosylated Hemoglobin and Glycated Albumin mentioning
confidence: 99%
“…Some scholars suggest that the elevation of HbA1C is associated with other maternal complications 18 , 30 , 45 , 47 , 56–58 (see Table 3 ). The ADA suggests that HbA1C<6 at mid-pregnancy is associated with the lowest risk of maternal complications.…”
Section: Application Of Glycosylated Hemoglobin and Glycated Albumin mentioning
confidence: 99%